METHODS OF LEARNING PHRASAL VERBS IN EFFECTIVE WAYS - Mamarajabova Sadoqat Dilmurod qizi, (Лучшие интеллектуальные исследования, 2024)
In this article, we can get information about learning English phrasal verbs in other languages in our republic and processes related to teaching, the ability to memorize new words of students taking into account the ways to successfully and effectively organize the study of new phrasal verbs.